The Influence of Leadership Style and Human Relations on Employee Performance with Mental Health Awareness as an Intervening Variable in Handicraft MSMEs in Garut Regency - Yuliani, Hani (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This research aims to analyze the influence of leadership style and human relations on employee performance with mental health awareness as an intervening variable. The research was conducted on 385 respondents who were handicraft MSMEs in Garut Regency using quantitative methods and the SEM-PLS approach. The research results show that leadership style and human relations have a significant effect on employee performance both directly and through mental health awareness. These findings reinforce the importance of psychological stability in supporting work performance. The analysis results show that leadership style has a significant influence on improving employee performance levels. It is proven that employee work quality, discipline, and productivity are improved by leaders who communicate openly, set an example, and motivate their subordinates. Furthermore, employee performance is improved through good interpersonal relationships, which include emotional support and mutual respect. Although most respondents have an understanding and behavior that supports their mental health, mental health awareness does not directly influence the relationship between leadership style and human relations on performance.